Feasibility study of oxidized naringin as a novel crosslinking agent for crosslinking decellularized porcine Achilles tendon and its potential application for anterior cruciate ligament repair. Issue 2 (24th August 2022) - Cheng, Can; Peng, Xu; Xi, Linjie; Luo, Yihao; Wang, Yuhang; Zhou, Yufan; Yu, Xixun
Abstract: Naringin (Nar), a natural flavanone glycoside, has been shown to possess a variety of biological activities, including anti‐inflammatory, anti‐apoptotic, bone formation, and so forth. In this study, Nar was oxidized by sodium periodate and the oxidized naringin (ONar) was used as a novel biological crosslinking agent. In addition, ONar‐fixed porcine decellularized Achilles tendon (DAT) was developed to substitute anterior cruciate ligament (ACL) for researching a novel ACL replacement material. The ONar with a 24 h oxidation time had appropriate aldehyde group content, almost no cytotoxicity, and a good crosslinking effect. The critical characteristics and cytocompatibility of ONar‐fixed DAT were also investigated. The results demonstrated that 1% ONar‐fixed DAT exhibited good resistance to enzymatic degradation and thermal stability as well as suitable mechanical strength. Moreover, 1% ONar‐fixed specimens exhibited excellent L929 fibroblasts‐cytocompatibility and MC3T3‐E1‐cytocompatibility. They also promoted the secretion of hepatocyte growth factor (HGF) and basic fibroblast growth factor (bFGF) from fibroblasts and bone morphogenetic protein‐2 (BMP‐2) from osteoblasts. And they also showed the good anti‐inflammatory properties in vivo experiments. Our data provided an experimental basis for ONar as a new cross‐linking reagent in chemical modification of DAT and ONar‐fixed DAT for ACL repair. Abstract :